A new species of Odontosyllis Claparède, 1863 (Annelida, Syllidae) with re-descriptions of O. liniata Hartmann-Schröder, 1962 and O. gymnocephala Hartmann-Schröder, 1965 - Verdes, Aida; Pleijel, Fredrik; Aguado, M. Teresa (Zootaxa, 2011)
Odontosyllis pentalineata, a new species from California is described. It differs from all other Odontosyllis species in the following characters: colour pattern consisting of five longitudinal black bands along body at median, dorso-lateral and lateral sides, a long pharynx with five large teeth directed backwards, and compound chaetae with short bidentate blades, slightly spinulated. Sequence data from COI are provided for molecular characterization. Additionally, the type species of O. liniata Hartmann-Schröder, 1962 and O. gymnocephala Hartmann-Schröder, 1965 are re-described based on type material.